Challenges and Remedial Strategies in Land Tax Collection in Medan Belawan: Qualitative Analysis with NVivo and Matrices of Framework - Daulay, Yulia; Aisyah, Siti (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research delves into the challenges and effectiveness of land and building tax (PBB) collection in Medan Belawan District over the period from 2019 to 2022. Through the utilization of Nvivo 11 software, the research employs qualitative methods, including interviews and data analysis, to uncover the intricacies of tax collection challenges in Medan Belawan District. The results aim to inform policymakers and tax authorities, providing insights to enhance the effectiveness of tax collection and promote taxpayer compliance. The findings reveal persistent shortcomings in achieving predetermined revenue targets, with various obstacles hindering the collection process. Non-delivery of Tax Payable Notices (SPPT) to taxpayers, inconsistent taxpayer residence data, limited economic conditions, and a lack of awareness among citizens regarding the significance of tax payments contribute to the inefficiency. To address these issues, the District has implemented measures such as checking taxpayer residence data, issuing warnings through environmental heads, and conducting outreach activities. However, the overall effectiveness of tax collection remains suboptimal. The study suggests that disparities in taxpayer data, insufficient awareness, and economic challenges are primary factors contributing to this ineffectiveness. Further efforts are recommended, including improved training programs, an incentive system based on work discipline, and increased community outreach to enhance understanding and compliance.